Analisis Digital Marketing dan Literasi Ekonomi Syariah Terhadap Pendapatan Pelaku Industri Kecil dan Menengah di Provinsi Lampung Melalui E-Commerce - Wahyu Pramana (Jurnal Ilmiah Ekonomi Islam, 2022)
The purpose of this research is to find out digital marketing and sharia economic literacy on the income of small and medium industry players in Lampung Province through e-commerce. Data obtained from the Department of Industry and Trade of Lampung Province were 19 small and medium industry then the data collected was 12 small and medium industry who were willing to become informants. The method used is a qualitative descriptive approach with a saturated sample. The results of the study show that all of the informants as many as 12 small and medium industry players use digital marketing and have implemented Islamic economic literacy. All small and medium industry players acknowledge an increase in income by using digital marking based on Islamic economic literacy. However, there are several small and medium-sized industry players who are more focused on serving consumers who buy offline on a large scale. It is hoped that further research can add any variables that can be linked